Semantic frames and semantic networks in the Health Science Corpus - Isabel Verdaguer (Estudios de Lingüística del Español)
The aim of this paper is to apply frame semantics principles to the analysis of a specialized corpus, the Health Science Corpus, implemented in the lexical database SciE-Lex. Taking FrameNet as the basis for this research, I will assign frame semantic features to Scie-Lex data in order to highlight the shared semantic and syntactic background of the related words in the biomedical register, give motivation to their patterns of collocates and establish frame-based semantic networks of related lexical units.